Answer:
(3, 1 )
Step-by-step explanation:
Given the 2 equations
y = - x + 4 → (1)
y = x - 2 → (2)
Substitute y = x - 2 into (1)
x - 2 = - x + 4 ( add x to both sides )
2x - 2 = 4 ( add 2 to both sides )
2x = 6 ( divide both sides by 2 )
x = 3
Substitute x = 3 into either of the 2 equations and solve for y
Substituting into (2)
y = 3 - 2 = 1
solution is (3, 1 )
Answer:
3 + 2n
Step-by-step explanation:
2 + 1 = 3.
2n cannot be added into this because it has a letter in front of it. Therefore, it stays on its own.
Answer:
From least to greatest: -2, 2/3
Step-by-step explanation:
Set each factor equal to 0 and solve
2x + 4 =0
2x = -4
x = -2
3x - 2 = 0
3x = 2
x = 2/3
Midsegments are line segments that connect the midpoints of a triangle. If we have the condition that QR = NP, we have the equation
3x + 2 = 2x + 16
Solving for x
3x - 2x = 16 - 2
x = 14
Therefore, x is 14. <span />